Shifting the balance: soluble ADAM10 as a potential treatment for Alzheimer's disease - Hershkovits, Ayelet Sarah; Gelley, Sivan; Hanna, Rawad; Kleifeld, Oded; Shulman, Avidor; Fishman, Ayelet (Frontiers in Aging Neuroscience, 2023)
Introduction: Accumulation of amyloid β in the brain is regarded as a key initiator of Alzheimer’s disease pathology. Processing of the amyloid precursor protein (APP) in the amyloidogenic pathway yields neurotoxic amyloid β species. In the non-amyloidogenic pathway, APP is processed by membrane-bound ADAM10, the main α-secretase in the nervous system. Here we present a new enzymatic approach for potential treatment of Alzheimer’s disease using a soluble form of ADAM10. Methods: The ability of the soluble ADAM10 to shed overexpressed and endogenous APP was determined with an ADAM10 knockout cell line and a human neuroblastoma cell line, respectively. We further examined its effect on amyloid β aggregation by thioflavin T fluorescence, HPLC and confocal microscopy. Using N-terminal and C-terminal enrichment proteomic approaches we identified soluble ADAM10 substrates. Lastly, a truncated soluble ADAM10, based on the catalytic domain, was expressed in E. coli for the first time and its activity evaluated. Results: The soluble enzyme hydrolyzes APP and releases the neuroprotective soluble APPα when exogenously added to cell cultures. The soluble ADAM10 inhibits the formation and aggregation of characteristic amyloid β extracellular neuronal aggregates. The proteomic investigation identified new and verified known substrates, such as VGF and N-cadherin, respectively. The truncated variant also exhibited α-secretase capacity as shown with a specific ADAM10 fluorescent substrate in addition to shedding overexpressed and endogenous APP. Discussion: Our in vitro work demonstrates that exogenous treatment with a soluble variant of ADAM10 would shift the balance towards the non-amyloidogenic pathway, thus utilizing its natural neuroprotective effect and inhibiting the main neurotoxic amyloid β species. The potential of such a treatment for Alzheimer’s disease needs to be further evaluated in vivo.